Do we need a practice incremental shuttle walk test for patients with interstitial lung disease referred for pulmonary rehabilitation?. Issue 3 (23rd January 2015) - Johnson‐Warrington, Vicki; Sewell, Louise; Morgan, Mike; Singh, Sally
Abstract Background and objective Patients with interstitial lung disease (ILD) are increasingly being referred to pulmonary rehabilitation (PR) where exercise capacity is measured, often by an incremental shuttle walk test (ISWT). These patients are frequently limited by severe dyspnoea and exertional desaturation. Available guidelines suggest two ISWT are needed; however, this is time consuming and it has not been reported whether a practice ISWT is necessary in ILD. We aimed to investigate if a practice ISWT is needed for patients with ILD referred to PR. Methods Patients with ILD who attended a PR assessment performed two ISWT as per standard protocol. Hospital notes were retrieved and relevant data extracted and validated. Endurance shuttle walk test (ESWT) level was calculated at 85% VO2 peak as estimated from the first ISWT (ISWT 1) and second ISWT (ISWT 2). Results Forty‐three patients were included (18 with idiopathic pulmonary fibrosis). There was a mean change of 28.84 (31.71) m between the two ISWT (P < 0.001) with 72.1% of patients walking further on ISWT 2. A Bland–Altman plot showed good agreement between the ISWTs; however, the limits of agreement were wide. There was a significant difference in ESWT levels (P < 0.001) when calculated from ISWT 1 and ISWT 2. ISWT 1 distance, post‐ISWT 1 heart rate and baseline Borg breathlessness score were significant variables (P < 0.05) in linear regression, but this only explained 42.6% of the variance (R2 0.426). Conclusions A practice ISWT is necessary to accurately assess exercise capacity. It was not possible to predict which patients did not need to complete two ISWT.